Phytochemical screening of the leaf and flower Extracts of five ipomoea species collected From in and around bangalore - SARINI.G; A.K.BOPAIAH (International Journal of Pharma and Bio Sciences, 2016)
The preliminary phytochemical analysis of plants will help in the identification of bioactive components present in each species, the knowledge of which, could help in comparing the differences between species and also in drug discovery.. A comparative study of secondary metabolites was done on Ipomoea obscura, Ipomoea quamoclit, Ipomoea palmata, Ipomoea indica and Ipomoea beraviensis using the leaf and flower extracts. Qualitative analysis was done for various constituents like Alkaloids, Flavonoids, Tannins, Saponins, Lignin’s, Terpenoids, Glycosides, Anthraquinone and Phlobatannins. The phytochemical screening revealed the presence of alkaloids and flavonoids invariably in all the extracts.